2005
DOI: 10.1161/circulationaha.105.533620
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Troponin Elevation, Cardiovascular Morbidity, and Outcome After Subarachnoid Hemorrhage

Abstract: Background-Cardiac troponin I (cTI) release occurs frequently after subarachnoid hemorrhage (SAH) and has been associated with a neurogenic form of myocardial injury. The prognostic significance and clinical impact of these elevations remain poorly defined. Methods and Results-We studied 253 SAH patients who underwent serial cTI measurements for clinical or ECG signs of potential cardiac injury. These patients were drawn from an inception cohort of 441 subjects enrolled in the Columbia University SAH Outcomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
225
3
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 304 publications
(248 citation statements)
references
References 26 publications
17
225
3
3
Order By: Relevance
“…The study concluded that cTnI elevation after SAH is associated with an increased risk of cardiopulmonary complications, delayed cerebral ischemia, and death or poor functional outcome at discharge. 17,43 Troponin elevation has also been reported in diabetic ketoacidosis. Metabolic derangement, fluid shifts, tachycardia, and increased sympathetic tone may trigger focal myocardial necrosis and Tn release.…”
Section: Clinical Significance Of Troponin Elevation In Absence Of Acmentioning
confidence: 92%
“…The study concluded that cTnI elevation after SAH is associated with an increased risk of cardiopulmonary complications, delayed cerebral ischemia, and death or poor functional outcome at discharge. 17,43 Troponin elevation has also been reported in diabetic ketoacidosis. Metabolic derangement, fluid shifts, tachycardia, and increased sympathetic tone may trigger focal myocardial necrosis and Tn release.…”
Section: Clinical Significance Of Troponin Elevation In Absence Of Acmentioning
confidence: 92%
“…6,7 Starting in May 2003, patients with SAH received EACA at the time of diagnosis. EACA (4 g IV) was administered as a loading dose followed by 1 g/h, with cessation of infusion 4 hours before angiography for a maximum duration of 72 hours after SAH onset.…”
Section: Methods Patientsmentioning
confidence: 99%
“…7 Deep venous thrombosis (DVT) was determined by Doppler ultrasonography. Outcome was assessed with the Modified Rankin Scale score at discharge and at 3 months.…”
Section: Study Outcomesmentioning
confidence: 99%
“…We also did not measure cardiac enzymes. Recent studies have shown that measurements of cardiac troponin I 30) and B-type natriuretic peptide 12) may provide additional prognostic information in SAH patients. Finally, the frequency and severity of arrhythmias were not determined, although continuous ECG monitoring did not demonstrate serious arrhythmias during the stay in the neurological care unit.…”
Section: Dysfunction In Sahmentioning
confidence: 99%